The mechanism of solid acid-catalyzed bamboo sawdust liquefaction under polyol systems - Wu, Bin; Tang, Hongwei; Huang, Yijia; Zhao, Mengke; Liang, Long; Xie, Zhanghong; Wei, Linshan; Fang, Guigan; Wu, Ting (Frontiers in Bioengineering and Biotechnology, 2024)
Solid acid catalysts are widely used in the field of biomass catalytic conversion owing to their advantages of low environmental pollution, easy separation and reusability. Nevertheless, there are relatively few studies on the mechanism of solid acid liquefaction for biomass. In this study, the effect of acid strength and acid amount of various solid acids on the liquefaction efficiency has been investigated using waste bamboo sawdust generated from the pulp and paper industry as the raw material. In addition, the physicochemical changes of cellulose, hemicellulose and lignin during the reaction process of bamboo sawdust have been studied, and the liquefaction mechanism of bamboo sawdust under the action of various solid acids has been concluded. As a result, the liquefaction efficiency of bamboo sawdust under the polyol system of PEG400/propanetriol is mainly related to the acid strength of the solid acid, and the greater the acid strength of the solid acid, the better the catalytic effect on the bamboo sawdust, in which the residual amount of bamboo sawdust liquefaction catalyzed by the SPA catalyst is only 17.72 %. Noteworthy, the most difficult component to liquefy is the crystallization of natural cellulose I into cellulose II during the reaction process, which is the primary obstacle to the complete liquefaction of bamboo sawdust by solid acid. Overall, these findings are valuable for the high value utilization of waste bamboo sawdust in the pulp and paper industry, as well as the application of solid acid catalytic technology for biomass.